Analysis of Pik3ca Gene Mutation along with Screening of Estrogen, Progesterone and Ki-67 Expression in Breast Cancer Cases - Bhuyan, Tandralee; Goswami, Ria; Saikia, Kandarpa Kr. (Asian Pacific Journal of Cancer Biology, 2026)
Analysis of Breast cancer exercised and contributed to the screening of the level of estrogen, progesterone and Ki-67 expression with prevalence rate of HER2/neu gene of mainly female population affected by breast cancer in Guwahati and along with detection of PIK3CA mutation in HER2/neu positive cases of other parts of the countries. A preliminary study conducted to analyze the prevalence, prognosis and treatment of breast cancer cases. In this study, we investigate the prevalence and expression patterns of estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2/neu gene, and identifies PIK3CA mutations in breast cancer patients from Guwahati, Northeast India, and other regions. A novel aspect of this study is the comparison of HER2/neu prevalence between Assam and other regions. Thus, the results indicated a lower HER2/neu positivity rate in Assam, with most affected individuals being housewives, that suggests unique regional risk factors. PIK3CA exon 20 mutations were identified in HER2- positive cases, potentially guiding targeted therapy.